Influence of network communities and transition to web 3.0 on change of approaches - Ramazanov, R.G.; Grinshkun, V.V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2018)
The article presents the genesis of network communities, the transformation of the interaction of participants in the evolution of this form of communication. The main characteristics and stages inherent in changing the formats of network interaction are described. The concept of networked communities is multifaceted and includes various processes of socialization: from the behaviour of people in interest groups to the formation of large international online communities. The evolution of such communities includes the transition from guest books and forums to more complex systems with many additional tools for networking. The introduction of modern technologies in all spheres of life leads to the formation of a qualitatively new distinctive model of education. In such conditions, the roles of participants in the educational process are changing, more attention is paid to self-education and development at the expense of the internal need for learning, the organizational and methodological component of the educational process is being reconstructed, and new conditions are created for the development of distance learning technologies. All this allows us to develop a more competitive system of interaction, make management processes transparent and create conditions for the independent development of each participant in the network space. Online network communities are a powerful tool that must be used in the education system in various interpretations, and as an additional resource that allows the principle of “lifelong learning” to be introduced into the teacher’s self-education system.